Biological treatment of high strength ammonia wastewater containing 2, 4-dichlorophenol in a membrane bioreactor: System performance and microbial community. (September 2019) - Li, Mingrun; Han, Fei; Meng, Zijun; Yang, Qingwei; Xu, Weiying; Wei, Dong; Du, Bin; Wei, Qin
Abstract: Two membrane bioreactors (toxic MBR and blank MBR) were established and compared to treat high ammonia wastewater in the presence and absence of 2, 4-dichlorophenol (2, 4-DCP). After 130 days operation, both MBRs expressed NH4 + -N removal efficiency (>95%) and 2, 4-DCP removal efficiency was (96.47 ± 1.54) %. Specific oxygen uptake rate (SOUR) data showed that nitrifying bacteria receive more severe inhibition than heterotrophic bacteria. Trans -membrane pressure (TMP) data indicated that the presence of 2, 4-DCP caused more serious membrane fouling. The protein/polysaccharide ratio increased to 1.1 and 6.3 in the loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS) after 2, 4-DCP addition. Excitation-emission matrix (EEM) showed that TB-EPS were mainly composed of aromatic and tryptophan PN-like substances, and LB-EPS of humic acid-like and fulvic acid-like substances. The microbial community analysis showed that the abundance of Proteobacteria, Firmicutes, and Nitrospirae under 2, 4-DCP stress increased from 22.56%, 27.10%, and 1.27% to 38.89%, 28.25% and 3.59%, respectively. Highlights: The degradation of 2, 4-DCP was evaluated in an MBR in 130 days operation. 2, 4-DCP affected MBR biological performance and membrane fouling behaviour. Main components of LB-EPS and TB-EPS from MBRs were identified by EEM Bacterial succession could facilitate the recovery of MBR performance.